RSA-OAEP Encryption with a Ciphertext Equality Testing Scheme in Intelligent Healthcare - Huijun Zhu; Tianfeng Li; Xiaobin Yan; Licheng Wang (Applied Sciences, 2026)
Driven by digital transformation, intelligent healthcare systems (IHS) have achieved the upgrading of modules covering diagnosis, treatment and public services. Against this backdrop, comprehensive security protection has become key for stabilizing the operation of medical systems and safeguarding patients’ legitimate rights and interests, as well as being an essential foundation for the sustainable development of IHS. Equality test function-based public key encryption (PKEwET) plays a vital role in IHS, the Internet of Things (IoT), etc. The scheme enables individual users to encrypt and store personal privacy data by themselves. Furthermore, it supports ciphertext matching and retrieval in a non-decryption manner in the public encryption system. To meet the needs of a variety of applications, many PKEwET applications for flexible authorization schemes have been proposed. In this paper, the equality test function is integrated with the Optimal Asymmetric Encryption Padding (RSA-OAEP) scheme. The aim is to offer an equality test function to RSA-OAEP algorithms without a secret key sk. In contrast to the original PKEwET primitive scheme, the proposed scheme integrates a flexible authorization mechanism. Authorized users can test the encrypted personal health information. Compared to the RSA-OAEP scheme, the proposed scheme in this paper supports the equality test function to the ciphertexts. The security of the proposed scheme is demonstrated to two different security levels, the OW-CCA level and the IND-CCA level. Finally, a performance analysis is presented. Appropriate comparisons with relevant works confirm that the proposed scheme offers a new function and shows good efficiency.